Farm Income Analysis of Shallot Farmers in Dulang, Enrekang, South Sulawesi - Indriani; Halimah Tussadia; Abdul Halim (Universitas Muhammadiyah Malang, 2023)
Shallot, recognized primarily as a spice vegetable, serves a pivotal role within the realm of vegetables. This study, undertaken in Dulang, Malua, Enrekang, South Sulawesi, Indonesia, a prominent hub for shallot production in the Enrekang Regency, involved 90 respondents comprising shallot farmers. The principal objective of this research is to ascertain the income generated by these farmers. Employing a survey method, the study gathered data through direct interviews with shallot farmers, selected through a simple random sampling approach. The findings revealed that the average yield from shallot cultivation ranged between IDR 40,000,000 and IDR 50,000,000 per harvest. This outcome suggests the economic viability of shallot production in Dulang, Malua, Enrekang, South Sulawesi, Indonesia.